Simultaneous use of black, green, and white certificates systems: A rather messy business - Eirik S. Amundsen; Torstein Bye (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2016)
We formulate a model with black, green and white certificates markets that function in conjunction with an electricity market. The markets function well in the sense that a common equilibrium solution exists, where all targets are satisfied (e.g. share of green electricity and share of energy saving/ efficiency increase.) The equilibrium solution adapts to changing targets (e.g. harsher target on energy saving), but it is in general impossible to tell whether this will lead to more, less, or unchanged consumption of "black", "green" or "white" electricity. These, markets give thus a poor guidance for future investments in green and white electricity. In order to get clear cut results, specific assumptions of parameter values and functional forms are needed. An example of this, based on a calibrated model founded on Norwegian data, is provided in the article. Also, gains and losses in terms of consumer's and producer's surpluses are calculated.
Keywords: C70; Q28; Q42; Q48; 330; renewable energy; electricity; Green Certificates; White Certificates